2019
DOI: 10.1021/acs.chemmater.9b04319
|View full text |Cite
|
Sign up to set email alerts
|

Native Defects and Their Doping Response in the Lithium Solid Electrolyte Li7La3Zr2O12

Abstract: The Li-stuffed garnets LixM2M 3 O12 are promising Li-ion solid electrolytes with potential use in solid-state batteries. One strategy for optimising ionic conductivities in these materials is to tune lithium stoichiometries through aliovalent doping, which is often assumed to produce proportionate numbers of charge-compensating Li vacancies. The native defect chemistry of the Li-stuffed garnets, and their response to doping, however, are not well understood, and it is unknown to what degree a simple vacancy-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 99 publications
4
78
0
Order By: Relevance
“…Previous investigations of native defects in SEs have put emphasis on strategies to improve ionic conductivity. [54][55][56]68,69 In this study, we focus on all native defects that may alter the concentration of charge carriers (electrons, holes), in addition to ionic carriers i.e., Li + and Na + ions. In a previous study, 55 we found V Na +Li +…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of native defects in SEs have put emphasis on strategies to improve ionic conductivity. [54][55][56]68,69 In this study, we focus on all native defects that may alter the concentration of charge carriers (electrons, holes), in addition to ionic carriers i.e., Li + and Na + ions. In a previous study, 55 we found V Na +Li +…”
Section: Discussionmentioning
confidence: 99%
“…[116] Such aliovalent doping strategies are common in inorganic SEs to introduce and charge-balance bulk defects favourable to ionic conduction, e. g. Li vacancies or interstitials. [117,118] Traditionally, EIS studies relevant to oxide SEs focused on new synthesis routes or to methods to increase the ionic conductivity, however recent work has investigated its fascinating interfacial properties with Li and several oxide-based devices have been reported.…”
Section: Oxide Electrolytesmentioning
confidence: 99%
“…The set of lithium ions that define a specific coordination polyhedron (all those within r coord of the central atom) can be described by a vertex list of these ion indices, e.g. (1,3,7,20,52,100). The edge topology connecting these ions is described by an undirected edge graph, where we consider an edge formed between any two vertices of a polyhedron with a separation smaller than a threshold distance r edge .…”
Section: S-limentioning
confidence: 99%
“…Although a number of highly conducting solid lithiumion electrolytes are known, none meet all the criteria for general commercial use [1,[4][5][6]. Identifying new solid lithium-ion electrolytes is an active area of research [3], with strategies ranging from targeted chemical modification of known solid electrolytes, to improve their conductivities [7][8][9][10][11], to high-throughput screening of new materials [12][13][14][15]. In both cases, it is useful to understand why some materials are highly-conducting, yet others are not * b.j.morgan@bath.ac.uk [3,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%